Investigation into the effect of skin tone modulators and exogenous stress on skin pigmentation utilizing a novel bioengineered skin equivalent. Issue 2 (26th September 2022) - Goncalves, Kirsty; De Los Santos Gomez, Paola; Costello, Lydia; Smith, Lucy; Mead, Hugh; Simpson, Amy; Przyborski, Stefan
Abstract: Human skin equivalents (HSEs) are a popular technology due to limitations in animal testing, particularly as they recapitulate aspects of structure and function of human skin. Many HSEs contain two basic cell types to model dermal and epidermal compartments, however this limits their application, particularly when investigating the effect of exogenous stressors on skin health. We describe the development of a novel platform technology that accurately replicates skin pigmentation in vitro. Through incorporation of melanocytes, specialized pigment producing cells, into the basal layer of the epidermis we are able to re‐create skin pigmentation in vitro. We observe apical distribution of melanin within keratinocytes and formation of supranuclear caps (SPNCs), only when the epidermal compartment is co‐cultured with a dermal compartment, leading to the conclusion that fibroblast support is essential for correct pigment organization. We also evaluate the commonly observed phenomenon that pigmentation darkens with time in vitro, which we further explore through mechanical exfoliation to remove a build‐up of melanin deposits in the stratum corneum . Finally, we demonstrate the application of a pigmented HSE to investigate drug modulation of skin tone and protection from UV‐induced damage, highlighting the importance of such a model in the wider context of skin biology.